1631. Made to Measure: Development of a Scoring Tool to Customize Antimicrobial Stewardship Goals Across a Large Health System. (26th November 2018) - Logan, Andrea Y; Williamson, Julie E; Jarrett, Steven; Davidson, Lisa E
Abstract: Background: The 2015 National Action Plan for Combating Antimicrobial Resistance called for a 20% decrease in antibiotic use among inpatients. Atrium Health (AH), formerly Carolinas HealthCare System, established reductions in antibiotic use (determined by days of therapy [DOT] per 1, 000 patient days [PD]) as a yearly system-wide quality goal since 2016. Hospitals in the AH inpatient network vary by size, scope, and antimicrobial stewardship program (ASP) maturity. Prior to our third year, we recognized the need to develop an objective method for determining antibiotic use reduction goals (AURGs); understanding that as ASPs mature, opportunities for reduction stabilize over time and may eventually plateau with consistent ASP. We sought to develop a tool that would better identify hospitals in need of aggressive AURGs. Methods: A scoring tool was developed to assess ASP implementation and metric achievement at individual hospitals to determine AURGs. Tool components were developed from ASP best practices and consensus among a multi-disciplinary team. The tool yields a maximal score of 41.5 points, with higher scores corresponding to more established ASPs who require less aggressive AURGs. An additional 6 points could be earned for tracked intervention data. Figure 1. Scoring Tool Components The tool was applied and a score calculated for each of 27 hospitals. Achieved score placed each hospital into one of 4 AURG ranges: maintain, 1–2.5%, 2.5–5%, and 5–7.5% of DOT/1000 PD. Goals were determined in relation to the median and 75th percentile scores. A minimum score of 39.5, representing full implementation of ASP score components, was required for a maintenance goal. Results: Scores ranged from 3 to 34.5 points across facilities (median 27.5; 75th percentile 31). Twelve facilities scored below 27.5 points, 10 hospitals between 27.5 and 31 points, and 5 facilities between 31 and 39.5 points corresponding to 5–7.5%, 2.5–5% and 1–2.5% AURGs, respectively. Figure 2. Facility Scores and AURGs Conclusion: Scores and corresponding AURGs were generally well accepted by stakeholders at facilities within the AH network. Next steps include examining the feasibility of achieving AURGs and obtaining feedback from facilities to refine the tool. The tool will also be applied to other healthcare networks to assess external validity. Disclosures: All authors: No reported disclosures.